2019
DOI: 10.1186/s13550-019-0532-7
|View full text |Cite
|
Sign up to set email alerts
|

Radiomic detection of microscopic tumorous lesions in small animal liver SPECT imaging

Abstract: Background Our aim was to present a new data analysis technique for the early detection of tumorous lesions using single-photon emission computed tomography (SPECT) imaging. Beyond standardized uptake value (SUV) and standardized uptake concentration (SUC), the skewness and kurtosis parameters of whole liver activity distribution histograms were examined in SPECT images to reveal the presence of tumorous cells. Methods Four groups of mice were used in our experiment: a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Compared to traditional image assessment, radiomics was a new tool that extracted image information through high-throughput methods to provide useful information for disease typing and grading, gene localization, early treatment, and prognostic assessment; Some studies had shown that radiomics had better diagnostic performance than traditional clinical in the non-invasive classification and diagnosis of diseases. Veres et al ( 28 ) showed that SPECT radiomics could identify microscopic lesions in the rat liver and suggested that the radiomics feature skewness could identify liver tumor lesions before they exhibit altered tissue function. Carabelli et al ( 29 ) demonstrated that the entropy of radiomic features in SPECT myocardial perfusion imaging (MPI) could evaluate coronary vascular microcirculation noninvasively and suggested that the improvement of left ventricular functional status by liraglutide would not improve the induction of coronary microvascular dysfunction in type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to traditional image assessment, radiomics was a new tool that extracted image information through high-throughput methods to provide useful information for disease typing and grading, gene localization, early treatment, and prognostic assessment; Some studies had shown that radiomics had better diagnostic performance than traditional clinical in the non-invasive classification and diagnosis of diseases. Veres et al ( 28 ) showed that SPECT radiomics could identify microscopic lesions in the rat liver and suggested that the radiomics feature skewness could identify liver tumor lesions before they exhibit altered tissue function. Carabelli et al ( 29 ) demonstrated that the entropy of radiomic features in SPECT myocardial perfusion imaging (MPI) could evaluate coronary vascular microcirculation noninvasively and suggested that the improvement of left ventricular functional status by liraglutide would not improve the induction of coronary microvascular dysfunction in type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…A higher LGRE value (representing a greater concentration of low gray-level values) predicted worse nodal response. Skewness has been used to characterize intratumoral heterogeneity [ 36 , 37 , 38 ]. Chen et al used skewness and minimum in a four-feature signature to classify lung nodules as benign or malignant on CT imaging [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Calculation of mice liver index was according to the following formula: [35] trueliver4ptindex=liver4ptweight/body4ptweight×1000.166667em% …”
Section: Methodsmentioning
confidence: 99%